2021
DOI: 10.3390/vaccines9080923
|View full text |Cite
|
Sign up to set email alerts
|

Do High Levels of Maternally Derived Antibodies Interfere with the Vaccination of Piglets against Porcine Circovirus Type 2? A Literature Review and Data Analysis

Abstract: Vaccination against porcine circovirus type 2 (PCV2) is commonly performed in piglets worldwide, and increasingly also in sows. We conducted a literature search and review to assess the potential interference of maternally derived antibodies (MDA) in piglets with vaccination against PCV2. The effectiveness of vaccination was compared to no vaccination in the presence of high levels of MDA (≥8 log2 IPMA titer), as reported in field studies. In total, 13 papers fulfilled the predefined inclusion criteria, allowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…These results are in line with several studies in which a clear interference of MDA in vaccine efficacy in terms of seroconversion has been shown [25,28,29,46,57]. However, a negative MDA effect on humoral immune response in piglets is suggested to be not related to a negative impact on vaccine efficacy except for those cases where MDA titres are high (≥8 log 2 IPMA antibodies) [26]. In addition, PCV-2 vaccines induce not only humoral immunity, but also a cellular immune response [13,30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in line with several studies in which a clear interference of MDA in vaccine efficacy in terms of seroconversion has been shown [25,28,29,46,57]. However, a negative MDA effect on humoral immune response in piglets is suggested to be not related to a negative impact on vaccine efficacy except for those cases where MDA titres are high (≥8 log 2 IPMA antibodies) [26]. In addition, PCV-2 vaccines induce not only humoral immunity, but also a cellular immune response [13,30].…”
Section: Discussionsupporting
confidence: 90%
“…PCV-2 vaccine efficacy in piglets has also been demonstrated in the face of maternally derived antibody (MDA) against PCV-2 [23]. However, the potential interference on vaccine efficacy produced by MDA has not been demonstrated under normal field conditions [24][25][26]. Interestingly, some studies have reported MDA interference with the development of a humoral response after vaccination [14,[27][28][29][30], while others have not [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, most of the studies available in the literature reporting PCV-2 MDA levels in vaccinated populations were focused on comparing the levels of antibodies present at the time of piglet vaccine administration, mostly around weaning [ 5 9 , 12 , 18 ]. The main objective behind such studies was to assess the effect exerted by certain PCV-2 MDA levels on the efficacy of the administered vaccine (reviewed by Poulsen-Nautrup et al [ 3 ]). As far as the authors’ knowledge, this is the first description of PCV-2-specific MDA titres in 3-day-old and 3-week-old piglets derived from sows vaccinated using different strategies.…”
Section: Discussionmentioning
confidence: 99%
“…PCV-2 vaccination can be applied to sows/gilts, sows and piglets, or piglets. From all these combinations, the most widely used at the field level is the immunization of piglets around weaning, but its application in sows is increasing worldwide [ 3 ]. Vaccination of sows against PCV-2 may seek two objectives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation